(untitled) (Revista Lusófona de Educação, 2025)
This paper discusses the role of digital technologies and environments (with emphasis on visual and multimedia technologies) in enhancing inclusive education for disabled or diverse learners. Drawing on five theoretical frameworks and related literature reviews, this research maps and highlights current accessible digital platforms, tools or software for Inclusive Digital Education (IDE), and their potential applications within main stream public education in Portugal. Based on statistics and empirical data collected from recent national and international studies and policy documents, the paper identifies key ‘facts and figures’ related to Portuguese inclusive education in recent years, including shifting conceptualizations of disability and diversity. The aim is to provide the research education communities with systematic and up-to-date information, documentation, and findings that emphasize the importance of critical perspectives and multifaceted approaches to the design, implementation and use of technologies and environments for IDE. Consideration for IDE is essential given the contemporary challenges and needs posed by an increasingly diverse and demanding student population in Portugal. Keywords: Inclusive Digital Education; Theoretical Frameworks for IDE; Design for Learning; Public Education; Portugal.